A Semiotic Analysis of Poem “Perfect” by Samantha King - Pasaribu, Bertha; Maisarah, Ira (English Education: Jurnal Tadris Bahasa Inggris, 2025)
This study used to analyze semiotics based on Roland Barthes' theory in Samantha King's poem titled "Perfect". The poem "Perfect" was selected for analysis because to its profound and intricate meanings, as well as its utilization of symbols to convey concealed significance and messages. The study used qualitative method  to find out semiotic analysis in the poem. Therefore the research aimed to find out the denotation, connotation and myth meaning based on Roland Barthes theory. The result showed  that the semiotic analysis of "Perfect" reveals how the poem critiques societal myths of perfection and identity. The denotative meaning revealed emotional struggles and self-imperfection, while the connotative meanings focused on the search for acceptance and healing. Barthes’ theory of myth showed how cultural norms of success and failure shape identity, leading to feelings of inadequacy and isolation. The poem is not only encouraged self-acceptance but also it is emphasizing that embracing imperfection is key to healing and self-discovery.